Ultra-rapid and automatic interplay between L1 and L2 semantics in late bilinguals: EEG evidence. (June 2022) - Bermúdez-Margaretto, B.; Gallo, F.; Novitskiy, N.; Myachykov, A.; Petrova, A.; Shtyrov, Y.
Abstract: Converging behavioral and neuroimaging evidence suggests parallel activation of native (L1) and second (L2) language codes in bilinguals, with the modulation of the N400 as the most likely neural correlate of such L1-L2 interplay at lexico-semantic level. However, this relatively late effect may reflect secondary controlled processes, in contrast to earlier modulations found in monolinguals (<200 msec) indicative of fast and automatic lexico-semantic L1 access, which has so far not been documented for bilingualism. To address this, we investigated early neurophysiological crosslinguistic activation during bilingual word access. EEG signals were recorded from a group of late bilinguals during a masked-priming crosslinguistic task in which L1 (Russian) words were presented as subliminal primes for 50 msec before L2 (English) target words. Prime-target pairs matched either phonologically only, semantically only, both phonologically and semantically, or did not match. Cluster-based random permutation analyses revealed a main effect of semantic similarity at 40–60 msec over centro-posterior scalp sites, reflecting a negative-going shift of ERP amplitudes for semantically similar prime-target pairs. Importantly, neural source reconstruction showed activations within a left-hemispheric network comprising the middle and superior temporal cortex and the angular gyrus as the most likely neural substrate of this early semantic effect. Furthermore, analyses also revealed significant differences over frontocentral sites for the main effect of semantic and phonological similarity, ranging from 312 to 356 and 380–444 msec respectively, thus confirming previously described N400 crosslinguistic effects. Our findings confirm the existence of an integrated brain network for the bilingual lexicon and reveal the earliest (∼50 msec) crosslinguistic effect reported so far, suggesting fast and automatic L1–L2 interplay, followed by later (possibly top-down controlled) processing stages.